How Can the Governance of the Municipality of Cajicá Be Affected by Integration into the Metropolitan Region? (2024)
The search to expand in Bogotá D.C. has led to the creation of a mechanism that allow the creation and regional integration of the municipalities of the savannah, developing regional proposals that allow a better development of the quality of life of the people, having impacts on social, environmental, economic, political and environmental issues. mobility, generating people find and in favor of developing the project called the Bogotá – Cundinamarca Metropolitan Region, and in this document the following may be identify the governance problems that the creation of the region would entail specifically in the municipality of Cajicá, since it is a concern latent for many citizens of the savannah who see as the problems that Bogotá has developed during its history can extend and fall on the municipalities of the savanna.